Study of macroglobulinaemia in Trypanosoma equiperdum infections of the rabbit - Ross, J M (Department of Molecular and Cell Biology, 2015)
1. 195 IgM, 75 IgM, and IgG were purified from the serum of Trypanosoma eguiperdum infected rabbits. The following antisera were also prepared for the quantitation of rabbit IgM and IgG: i. goat anti rabbit IgM antiserum; ii. goat anti rabbit IgG antiserum; iii. goat antiserum to rabbit serum proteins. 2. The serum levels of 195 IgM, measured by gel diffusion and rocket immunoelectrophoresis were shown to increase approximately ten times at the peak of the Trypanosoma eguiperdum infections in the rabbit. The serum IgG. concentrations, measured by gel diffusion increased more than seven times.aver the infection period. Low molecular weight 75 IgM was also detected in the serum by rocket immunoelectraphoresis and quantitative gel diffusion, but accurate concentration determinations could not be made. 3. Rheumatoid factors were not detected by passive haemagglutination and latex fixation tests, despite the use of a variety of sensitizing globulins. These results failed to confirm earlier reports of the presence of rheumatoid factors in infected rabbits. 4. After separation of the 75 and 195 fractions by density gradient centrifugation, both fractions were found by complement fixation to contain anti trypanosome antibodies. These antibodies were also detected by immunofluorescence in the serum and 75 fractions, and by agglutination in the 195 fractions. 5. The 195 fractions also contained complement fixing antibodies reacting with the tissue antigens of rabbit liver, heart and kidney. Maximum titres of 1/80 - 1 /160 were found at the peak of the infection. Absorption of the rabbit sera with trypanosomes indicated that the trypanosomal and tissue antibodies were distinct.